Developing biophilic walkability framework for sustainable development in Malaysia / Nurul Hazimah Hanim Mohd Zubir - Mohd Zubir, Nurul Hazimah Hanim (Universiti Teknologi MARA (UiTM), 2025)
Existing pedestrian often lacks essential features such as connectivity, cover, and shade, which are crucial for creating comfortable and enjoyable walking experiences. Poor sanitation, inadequate street maintenance, and insufficient accommodations for individuals with special needs further exacerbate these issues, making walking an unattractive and inconvenient option for many. The tropical climate, characterized by high temperatures and humidity, also discourages walking by adding discomfort and exhaustion to the experience. Consequently, reliance on motorized transport has increased, leading to greater greenhouse gas emissions, traffic congestion, reduced physical activity levels, and diminished opportunities for social interaction. Amidst these concerns, biophilic design is increasingly recognized as a crucial strategy for sustainable urban development.